2022
DOI: 10.1590/1516-3180.2021.0298.r1.27052021
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the neutrophil-to-lymphocyte ratio in predicting the severity of COVID-19 patients: a retrospective cohort study

Abstract: In December 2019, a novel coronavirus named severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), was identified in Wuhan, China, and it spread rapidly all over the world. 1 The World Health Organization (WHO) gave the name coronavirus disease-19 to the resultant disease and declared it to be an epidemic. 2 The first polymerase chain reaction (PCR)-positive COVID-19 case in Turkey was detected on March 11, 2020. 3 In some studies in the literature, it was reported that 14% of COVID-19 patients deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Limitations and Strengths. This study has limitations: (1) the study population corresponded only to older adults insured by EsSalud, who have particular sociodemographic characteristics, and does not represent all older Peruvian adults; however, EsSalud insures nearly a third of the Peruvian population [58]; (2) some of the variables included have missing values (as laboratory markers including neutrophils, lymphocytes, and platelets) because they were not measured at hospital admission; however, the adjusted regression model was developed considering only those with a percentage of missing values less than 20%; (3) we conducted this study with data collected during the first wave of COVID-19 in Peru, which could be relevant within the Peruvian context, in which not many articles have been published and these studies could help us better understand what happened during that pandemic period and be prepared for future pandemics; (4) this study was carried out during a prevaccine era; however, studies developed during the postvaccine distribution era described results similar to ours [59][60][61]; (5) among laboratory markers, some, which are considered relevant, such as cytokines, were not measured in this study; however, the variables most accessible and practical according to the literature were used. Despite these limitations, this study represents one of the first to evaluate the role of the NLR and the PLR as predictors of mortality in older adults with COVID-19 [12].…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…Limitations and Strengths. This study has limitations: (1) the study population corresponded only to older adults insured by EsSalud, who have particular sociodemographic characteristics, and does not represent all older Peruvian adults; however, EsSalud insures nearly a third of the Peruvian population [58]; (2) some of the variables included have missing values (as laboratory markers including neutrophils, lymphocytes, and platelets) because they were not measured at hospital admission; however, the adjusted regression model was developed considering only those with a percentage of missing values less than 20%; (3) we conducted this study with data collected during the first wave of COVID-19 in Peru, which could be relevant within the Peruvian context, in which not many articles have been published and these studies could help us better understand what happened during that pandemic period and be prepared for future pandemics; (4) this study was carried out during a prevaccine era; however, studies developed during the postvaccine distribution era described results similar to ours [59][60][61]; (5) among laboratory markers, some, which are considered relevant, such as cytokines, were not measured in this study; however, the variables most accessible and practical according to the literature were used. Despite these limitations, this study represents one of the first to evaluate the role of the NLR and the PLR as predictors of mortality in older adults with COVID-19 [12].…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…Therefore, early risk prediction tools in ED admissions of geriatric patients have been an important research topic in the literature. The inflammatory reaction plays a significant role in the pathophysiology of COVID-19 19 . Therefore, inflammatory markers such as CRP have been studied as prognostic indicators of COVID-19 20 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, severe cases are associated with increased NLR values, higher than ≥3.13, or higher than ≥5.0 17,23 . Yılmaz et al conducted a retrospective cohort study among 1175 COVID‐19 patients, and showed that NLR cut off value of 5.14 was a significant predictor of the need for ICU (sensitivity: 77.87%, and specificity: 74.08%) and hospital mortality (sensitivity: 77.27%, and specificity: 75.82%) 9 . However, a low number of patients had CKD in the study cohort ( n = 87), and there was no data regarding end‐stage renal disease in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Increased NLR is a well‐defined risk factor for variety of medical conditions such as major cardiac events, sepsis and poor prognosis in cancer 6 . Similarly, recent studies suggested that the NLR could provide rapid insights regarding early recognition of critical illness and whose prognosis among COVID‐19 patients 7–9 . On the other hand, patients with chronic kidney disease (CKD) have a chronic inflammatory process, which may affect the predictive value of NLR in MHD.…”
Section: Introductionmentioning
confidence: 99%